ARSITEKTUR CLOUD NETWORKING UNTUK MIGRASI INFRASTRUKTUR TELEKOMUNIKASI KE PUBLIC CLOUD: TINJAUAN SISTEMATIK - Sultha Redysa; Andi Ahmad Dahlan; Yulindon Yulindon (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
This study examines the transformation of telecommunication network architectures toward public cloud environments through a cloud networking approach. Although technologies such as Network Function Virtualization (NFV), Software Defined Networking (SDN), edge computing, and virtualization have developed rapidly, the integration of cloud networking architectures capable of supporting comprehensive multi-domain communication remains limited. This research employs a Systematic Literature Review (SLR) of publications from 2020–2024 to identify development trends, challenges, and research gaps in cloud networking architectures. The analysis indicates that multi-domain interconnection, particularly communication among cloud, edge, and virtual networks, remains a major unresolved challenge, while most studies still focus on optimizing individual components rather than comprehensive architectural integration. As its main contribution, this study proposes the Hierarchical Multi-Domain Cloud Networking Fabric (HM-CNF), integrating multiple communication mechanisms into a hierarchical unified system to enable more coordinated, scalable, and efficient multi-domain communication, supporting telecommunication infrastructure migration toward public cloud and providing a conceptual framework for next-generation cloud networking systems.